INVESTIGATION OF ACCD3 GENE OF MYCOBACTERIUM TUBERCULOSIS IRAQI ISOLATES - Abdul-Jalil, Asra’a A; Al-khafaji, Zahra M; Al-ouqaili, Mushtak T (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Mycobacterium tuberculosis, one of the deadliest human pathogens, causes several million new infections and about 2 million fatalities annually. The cell wall of M. tuberculosis is endowed with a highly impermeable, complex array of diverse lipids such as mycolic acids, which bestow the bacterium with not only virulence but also resistance to host immunity and antibiotics. Methods: Mycobacterial lipid metabolism has thus emerged as an attractive target for the design and development of novel antimycobacterial therapeutics. The first committed step in the biosynthesis of mycolic acid is the carboxylation of acetyl-CoA to malonyl-CoA which is catalyzed by acetyl-coenzyme A carboxylase carboxyl transferase beta subunit (accD3), a primer pairs were designed computationally and used for the amplification of accD3 gene using conventional polymerase chain reaction (PCR) and sequencing the PCR product and analyze the results. Results: Two sequences of the detection gene (LprM gene) and eight sequences of accD3 gene under study were deposited at NCBI – GenBank database with accession numbers (LC009881, LC009880.1, LC006979, LC008196, LC009412, LC009414, LC034168, LC038020, LC041163, and LC041368) and primer pairs deposited at Probe database/NCBI with accession number Pr032816836. Conclusion: AccD3 gene is a good drug target in MDR M. tuberculosis strains.